Assessment of the Risk of Development Accidents in Odontogenic Pyoinflammatory Diseases - Mustafaev, Magomet (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: For full-fledged diagnostics and prognosis of the course of odontogenic infectious diseases, we should have information about main pathogenetically significant factors of species and adaptive immunity, and we also need to take into account the characteristics of etiological agents. The aim of the research: To reveal the main factors of the complicated course of odontogenic pyoinflammatory diseases of the maxillofacial area. Results: The most significant indicators, which were studied in this research, during expectancy of course of the odontogenic pyoinflammatory diseases of the maxillofacial area are as follows: (a) Low level of intracellular production of radicals; (b) low level of antioxidant capacity of blood plasma of patients on the second day of hospitalization; (c) high level of cytokines of the proinflammatory group (interleukin-1β [IL-1β], IL-6, tumor necrosis factor alpha [TNF-α]) and low level of IL-10 in the blood plasma of patients during first day of hospitalization, which remaining for 7–10 days against the background of the ongoing therapy; (d) low concentration of TNF-α in the blood plasma of patients with acute odontogenic osteomyelitis on the first day of hospitalization; (e) a considerable proportion of strictly anaerobic pathogens as a part of the mixed microflora of a purulent discharge. Conclusions: The most significant risk factors for accidents in odontogenic pyoinflammatory diseases include such as disturbance of effector properties of leukocytes, imbalance of mediator regulation of inflammation, and predominance of strictly anaerobic microflora.